Association between malaria exposure and Kaposi's sarcoma‐associated herpes virus seropositivity in Uganda. Issue 5 (9th February 2015) - Nalwoga, Angela; Cose, Stephen; Wakeham, Katie; Miley, Wendell; Ndibazza, Juliet; Drakeley, Christopher; Elliott, Alison; Whitby, Denise; Newton, Robert
Abstract Objective Unlike other herpes viruses, Kaposi's sarcoma‐associated herpes virus (KSHV) is not ubiquitous worldwide and is most prevalent in sub‐Saharan Africa. The reasons for this are unclear. As part of a wider investigation of factors that facilitate transmission in Uganda, a high prevalence country, we examined the association between antimalaria antibodies and seropositivity against KSHV. Methods Antibodies against P. falciparum merozoite surface protein (PfMSP)‐1, P. falciparum apical membrane antigen (PfAMA)‐1 and KSHV antigens (ORF73 and K8.1) were measured in samples from 1164 mothers and 1227 children. Results Kaposi's sarcoma‐associated herpes virus seroprevalence was 69% among mothers and 15% children. Among mothers, KSHV seroprevalence increased with malaria antibody titres: from 60% to 82% and from 54% to 77%, comparing those with the lowest and highest titres for PfMSP‐1 and PfAMA‐1, respectively (P < 0.0001). Among children, only antibodies to PfAMA‐1 were significantly associated with KSHV seropositivity, (P < 0.0001). In both mothers and children, anti‐ORF73 antibodies were more strongly associated with malaria antibodies than anti‐K8.1 antibodies. Conclusion The association between malaria exposure and KSHV seropositivity suggests that malaria is a cofactor for KSHV infection or reactivation.